Imposter Phenomenon Among the Final Year (Part 1 and 2) Medical Students of a Private Medical College in the Union Territory of Puducherry: A Cross Sectional Study - C, Padma Priya; Konduru, Rajesh Kumar; M, Manikandan; Purty, Anil J (Indian Journal of Community Health, 2024)
Introduction: “Imposter syndrome” or “Imposter Phenomenon” is not a mental disorder but is considered as a psychological pattern in which people doubt their accomplishments and is associated with certain poor psychological functioning like low self-esteem can be detrimental to medical students. Objective: To find out the prevalence of Imposter phenomenon as well as it association with self-esteem among the final year medical students. Methods: A cross sectional study was carried-out among 249 medical students of a private medical college in the U.T of Puducherry using Clance Imposter Phenomenon scale. Results: 58.2% and 41.8% of the participants were in Part-1 and part-2 of final year respectively. It was observed that every participant had some degree of Imposter phenomenon. Low self –esteem, was found among 12.85% of the study participants. In this study there was no association between the low self-esteem and Imposter Syndrome. Conclusion: It is very clear that the burden of Imposter syndrome is quite high among the medical students as the reasons are varied. Extensive research to elaborate these is the need of the hour, as this information helps in designing the preventive measures for the students who are the future of the nation and the foundation stones of progress.